1996
DOI: 10.1107/s0108768195008512
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystal structure analysis and energy minimizations of a MFI-type zeolite at low p-dichlorobenzene sorbate loading

Abstract: The crystal structure of a low-loaded adsorption complex of H-ZSM-5 with p-dichlorobenzene has been studied by single-crystal X-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
46
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 9 publications
2
46
0
Order By: Relevance
“…Many structures consisting of MFI-type zeolites loaded with aromatic compounds have been determined using single-crystal XRD. [19][20][21][22][23][24][25][26] However, there are no reports concerning the locations of non-aromatic hydrocarbons, despite the heightened interest in this subject. These structures have not yet been determined due to the twinning problem, which makes the crystallographic analysis highly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Many structures consisting of MFI-type zeolites loaded with aromatic compounds have been determined using single-crystal XRD. [19][20][21][22][23][24][25][26] However, there are no reports concerning the locations of non-aromatic hydrocarbons, despite the heightened interest in this subject. These structures have not yet been determined due to the twinning problem, which makes the crystallographic analysis highly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that aromatic molecules, such as p -xylene, p -dichlorobenzene, and trans -stilbene, preferentially adsorb at different locations of the framework depending not only on the adsorbate nature but also on the adsorbate loading. 14 19 Techniques such as single-crystal X-ray diffraction and high-resolution synchrotron X-ray powder diffraction showed that at low loadings, the adsorbate molecules are preferentially located inside in the straight pores of ZSM-5 crystals, 14 16 whereas at high loadings, they accumulate at pore intersections and in the sinusoidal pores. 18 , 19 In addition, Eckman et al used deuterium solid-state NMR to trace temperature-dependent changes in orientation of p -xylene molecules in H-ZSM-5 at low loadings.…”
mentioning
confidence: 99%
“…As mentioned earlier, it has been described in the literature that the pore preference of p -dichlorobenzene depends on the adsorbate loading. 14 , 18 On this basis, we speculated that it should be possible to affect the pore preference of the catalytic reaction and direct the reaction to predominantly happen in one of both pore types. Numerous microspectroscopic studies have been conducted in the past to investigate the factors affecting catalytic activity of H-ZSM-5, such as its relation with the subcrystalline intergrowth structure, 24 26 , 29 33 the effect of commonly applied steaming treatments, 34 , 35 the mechanisms of coke formation, 36 and the solvent effect.…”
mentioning
confidence: 99%
“…Studies to clarify the structures of sorbates in the ZSM-5 framework have been widely reported; single crystal X-ray diffraction is the most suitable method for elucidating these structures. Investigations of the sorbate-ZSM-5 structure by X-ray diffraction have been reported for toluene [1], naphthalene [2], dichlorobenzene [3,4], pnitroaniline [5,6], and many others.…”
Section: Introductionmentioning
confidence: 98%
“…However, the quality of most synthesized crystals is too low for single crystal X-ray diffraction. Lermer's synthesis is the best method thus far reported for producing large high-quality crystals [12][13][14]; this method was utilized in most of the sorbate-ZSM-5 investigations mentioned above [1][2][3][4]6]. However, this method also produces large quantities of the by-product analcime (Na 8 Al 8 Si 16 O 48 Á 8 H 2 O) ( Fig.…”
Section: Introductionmentioning
confidence: 98%